Pudeur et impudeur comme modalités de construction d’un corps politique chez Hervé Guibert - Genon, Arnaud (Romanica Silesiana)
Modesty and Immodesty as a Modality of Construction of a Political’s Body in Hervé Guibert’s Work Modesty and immodesty are two movements used by Hervé Guibert to build a unique picture of his body that I propose to examine in this article in order to highlight a politics of the Guibertian’s body. The multiple body escapes any form of confinement, restriction and constructs itself without any sign of sexual normativity. Guibert refuses both heterosexual and homosexual models and anchors himself in another space, uncertain and undefined. Key words: Hervé Guibert, political’s body, modesty and immodesty.